Response to environmental perturbations in microbial nutrient-cycling ecosystems - Bush, Timothy (The University of Edinburgh, 2015)
The habitability of Earth is dependent upon the global recycling of elements essential for life, such as nitrogen, sulfur and carbon. Nutrient-cycling by micro-organisms is vital to these biogeochemical cycles because many key steps are mediated primarily, or exclusively, by microbial life. The dynamics of these cycles are highly complex, and environmental perturbations (such as changes in the oceanic oxygen concentration) can have unexpected or catastrophic effects; often causing abrupt switches between chemical states. Despite the importance of these environmental perturbations however, few theoretical models have addressed how they affect the dynamical behaviour of nutrient-cycling microbial ecosystems. In this work, we investigate the effect of environmental perturbations on microbially-mediated nutrient cycles and assess the likelihood of "sudden transitions" between chemical states of the ecosystem occurring in a variety of ecological contexts. To do this, we first use computational modelling of microbial nutrient-cycling, using a "box model" approach. We then move on to an experimental study using the microbial sulfur cycle as a model ecosystem, with freshwater pond sediment/water microcosms. These microcosms have the advantage of retaining many of the features of the real ecosystem (such as microbial diversity, spatial structure, and abiotic interactions) while allowing the controlled manipulation of environmental perturbations. We study these microcosms using a combination of chemical measurements and high-throughput sequencing of the microbial community. Finally, we return to the computational side, and attempt to reproduce chemical data from our experiments in a mathematical model containing realistic abiotic chemical interactions.
Keywords: microbial communities; mathematical models; environmental changes; nutrient availability.; microbial ecosystems